Self-assembled alpha-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material as well as preparation method and application thereof

By self-assemblying the combination of α-cobalt hydroxide/manganese oxide composite material and nickel mesh, the problems of low oxygen evolution reaction efficiency and high overpotential in the prior art are solved, and a more efficient and economical process of electrolyzing hydrogen production is achieved.

CN119640315APending Publication Date: 2025-03-18SHANDONG JIANZHU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411812143.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing alkaline electrolytic hydrogen production technology, the oxygen evolution reaction (OER) kinetic process is slow and requires a high overpotential, resulting in higher electrode efficiency and electricity consumption costs.

Method used

Using self-assembled α-cobalt hydroxide/manganese oxide composite electrocatalytic oxygen evolution material, an α-cobalt hydroxide/manganese oxide nanocrystals were assembled on a nickel net to prepare an α-cobalt hydroxide/manganese oxide@nickel grid electrode for alkaline electrolysis of hydrogen production process.

Benefits of technology

The catalytic activity of the electrode is improved, the overpotential and taffel slope are reduced, the stability and electrochemical active area of ​​the electrode are enhanced, and the hydrogen production efficiency is improved and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640315A_ABST
    Figure CN119640315A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano functional materials and electrochemical catalysis, and particularly relates to a self-assembled alpha-cobalt hydroxide / manganese oxide composite electro-catalytic oxygen evolution material as well as a preparation method and application thereof. An alpha-cobalt hydroxide / manganese oxide (alpha-Co (OH) 2 / MnO) composite material is prepared from cobalt hydroxide nanotubes and manganese oxide nanocrystals and is loaded to a nickel net (Ni) to manufacture an alpha-cobalt hydroxide / manganese oxide nickel net electrode (alpha-Co (OH) 2 / MnO Ni), the electrode can be used as a working electrode, the process of producing hydrogen by electrolyzing water is realized under the alkaline condition, and the hydrogen production efficiency is improved. And a simple, efficient, convenient and economical new thought is provided for hydrogen preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano functional materials and electrochemical catalysis, and specifically relates to an alpha-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] As fossil energy is increasingly depleted, hydrogen energy has become an ideal strategic energy source for deep decarbonization and clean energy transformation due to its green and clean, high mass energy density, and wide sources. Therefore, finding an efficient, economical, and stable hydrogen production technology is of great significance to energy strategy.

[0004] Among various hydrogen production technologies, water electrolysis hydrogen production technology has the advantages of abundant raw materials and high purity of hydrogen production, and is the most promising hydrogen energy technology for large-scale application. Water electrolysis hydrogen production technologies mainly include alkaline water electrolysis hydrogen production technology, proton exchange membrane water electrolysis hydrogen production technology, high-temperature solid oxide water electrolysis hydrogen production technology, and anion exchange membrane water electrolysis hydrogen production technology. Among them, alkaline water electrolysis hydrogen production technology has the highest degree of commercialization, but due to the slow kinetics of the oxygen evolution reaction (OER) and the need for a high overpotential, its development process is greatly restricted by electrode efficiency and electricity costs.

[0005] At present, the OER performance of nickel mesh or nickel foam electrodes widely used in commercial electrolyzers still has a lot of room for improvement. A composite nickel-based catalytic functional layer is prepared on a nickel mesh or nickel foam substrate. The OER performance of the nickel-based self-supporting electrode is improved by enhancing the conductivity of the catalytic functional layer and the synergistic effect between metals, increasing the number of active sites, reducing the diffusion path, and changing the surface atomic configuration. This is of great significance for developing new high-activity oxygen evolution electrodes, improving electrode efficiency, and reducing hydrogen production costs. Summary of the invention

[0006] In view of the above-mentioned problems, the purpose of the present invention is to provide a self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material and its preparation method and application. The present invention uses cobalt hydroxide nanotubes and manganese oxide nanocrystals to prepare α-cobalt hydroxide / manganese oxide (α-Co(OH)2 / MnO) composite materials, and loads them onto nickel mesh (Ni) to make α-cobalt hydroxide / manganese oxide@nickel mesh electrode (α-Co(OH)2 / MnO@Ni), which can be used as a working electrode to realize the process of hydrogen production by electrolysis of water under alkaline conditions, providing a simple, efficient, convenient and economical new idea for realizing the production of hydrogen.

[0007] Specifically, the present invention provides the following technical solutions:

[0008] The first aspect of the present invention provides a self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material, wherein the composite material comprises cobalt hydroxide nanotubes and manganese oxide nanocrystals distributed in the cobalt hydroxide nanotubes; the diameter of the cobalt hydroxide nanotubes is 12 to 15 nm, and the average particle size of the manganese oxide nanocrystals is 11 to 13 nm.

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material, comprising the following steps:

[0010] S1, mixing CoSO4·7H2O and trimethyltetradecylammonium chloride in an organic solvent for solvothermal reaction to obtain α-Co(OH)2 nanotubes, and further obtaining α-Co(OH)2 nanotube dispersion;

[0011] S2, mixing Mn3O4, oleic acid, 1-octadecyl alcohol and 1-octadecene for heating reaction to obtain MnO nanocrystals, and further obtaining a MnO nanocrystal dispersion;

[0012] S3. After the MnO nanocrystal dispersion is naturally volatilized, α-Co(OH)2 nanotube dispersion is added, and ethanol is added, and after standing, a self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material is obtained.

[0013] Preferably, in step S1, the mass ratio of the CoSO4·7H2O to trimethyltetradecylammonium chloride is 4 to 5:1.

[0014] Preferably, in step S1, the organic solvent is selected from one or more of octane, hexane or a mixed solvent of octane and hexane; further preferably, the organic solvent is a mixed solvent of octane and hexane, and the volume ratio of octane to hexane in the mixed solvent is 1:17-20.

[0015] Preferably, in step S1, the temperature of the solvent thermal reaction is 120-150° C., and the time is 8-15 h; further preferably, the temperature of the solvent thermal reaction is 140° C., and the time is 10 h.

[0016] Preferably, in step S1, the product obtained by the solvothermal reaction is washed in an ethanol-n-hexane cycle to finally obtain pure α-Co(OH)2 nanotubes, and then dispersed in a chloroform solvent to obtain an α-Co(OH)2 nanotube dispersion.

[0017] Preferably, in step S2, the usage ratio of Mn3O4, oleic acid, 1-octadecyl alcohol and 1-octadecene is 0.2-0.25 g: 5-6 mL: 1.2-1.6 g: 8-12 mL.

[0018] Preferably, in step S2, the heating reaction is first heated to 180-220° C., kept warm for 25-35 min, then heated to 300-350° C., kept warm for 25-35 min, and kept warm for another 25-35 min when the color of the reaction solution changes, to form MnO nanocrystals.

[0019] Further preferably, the heating reaction is first heated to 200° C., kept warm for 30 minutes, then heated to 320° C., kept warm for 30 minutes, and kept warm for another 30 minutes when the color of the reaction solution changes, to form MnO nanocrystals.

[0020] Preferably, in step S2, the heating reaction is carried out under an inert atmosphere; the inert atmosphere is selected from one or more of hydrogen, nitrogen and argon.

[0021] Preferably, in step S2, the product obtained by the heating reaction is washed in an ethanol-n-hexane cycle to finally obtain MnO nanocrystals, and then dispersed in n-hexane to obtain a MnO nanocrystal dispersion.

[0022] Preferably, in step S3, the standing time is 20 h to 40 h, preferably 24 h.

[0023] Preferably, in step S3, the product after standing is washed, dried and annealed to obtain a self-assembled α-cobalt hydroxide / manganese oxide composite material;

[0024] Preferably, the annealing temperature is 280-350° C., and the time is 25-40 min. More preferably, the annealing temperature is 300° C., and the time is 30 min.

[0025] The third aspect of the present invention provides a working electrode, comprising the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material described in the first aspect.

[0026] Preferably, the working electrode is prepared by adding ground α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material into an ethanol solution, mixing with a binder solution, and then ultrasonically treating the mixture, coating the obtained slurry on a nickel mesh, and drying the mixture.

[0027] Further preferably, the mass fraction of the naphthol resin solid content in the binder solution is 5%; the dosage ratio of the α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material to the binder solution is 1 mg:1 μL, and the mass percentage of the naphthol solution is 5%; the ultrasonic treatment time is 0.5 to 2 h;

[0028] The coating method is to evenly coat the slurry on one end of the nickel mesh, with each coating range of 0.02 to 0.03 cm 2 The size of the nickel mesh is 1 cm*0.5 cm; the coating area is 0.5 cm*0.5 cm, and the α-Co(OH)2 / MnO@Ni electrode is obtained after drying.

[0029] The third aspect of the present invention provides the use of the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material described in the first aspect and / or the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material prepared by the preparation method described in the second aspect as an oxygen evolution electrode.

[0030] The fourth aspect of the present invention provides the use of the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material described in the first aspect and / or the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material prepared by the preparation method described in the second aspect in the field of hydrogen production by electrolysis of water.

[0031] One or more embodiments of the present invention have at least the following beneficial effects:

[0032] (1) The α-Co(OH)2 / MnO composite material obtained by the self-assembly method of the present invention has a simple preparation method and low production cost, and can be directly used as an alkaline water electrolysis hydrogen production electrode without further modification.

[0033] (2) Compared with the α-Co(OH)2@Ni electrode and the MnO@Ni electrode, the α-Co(OH)2 / MnO@Ni electrocatalytic active material prepared by the present invention has a larger electrochemical active area, which can expose more active sites, thereby increasing the contact area between the electrode and the electrolyte and accelerating the electron transfer rate during the reaction.

[0034] (3) Compared with the commercial IrO2@Ni electrode, α-Co(OH)2 / MnO@Ni exhibits superior catalytic activity in alkaline electrolytes with a lower overpotential (η 50 =310mV), lower Tafel slope (59.62mV / dec) and good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0036] Figure 1The electron microscope pictures of various materials prepared by the present invention are shown in FIG. 1 , wherein (a) is a transmission electron microscope picture of α-Co(OH)2 nanotube material; (b) is a transmission electron microscope picture of MnO nanocrystal material; (c) is a transmission electron microscope picture of α-Co(OH)2 / MnO composite material; (d) is a scanning electron microscope picture of α-Co(OH)2 / MnO after annealing;

[0037] Figure 2 The XRD spectrum of the α-Co(OH)2 / MnO composite material prepared by the present invention, wherein (a) is the XRD spectrum of the composite material before annealing, and (b) is the XRD spectrum of the composite material after annealing;

[0038] Figure 3 The electrochemical impedance spectra of the electrode materials prepared in Example 1 and Comparative Examples 1-2 are shown;

[0039] Figure 4 C of the electrode material prepared in Example 1 and Comparative Examples 1-2 dl Fitting curve graph;

[0040] Figure 5 OER linear sweep voltammetry curves of four electrodes prepared by IrO2@Ni commercial electrode, Example 1, and Comparative Examples 1-2 in 1M KOH solution. DETAILED DESCRIPTION

[0041] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0042] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0043] The small amount and multiple times coating method involved in the embodiments and comparative examples of the present invention refers to: taking 5 mg of the sample and adding it to 450 μL of ethanol, adding 5 μL of naphthol solution (5% wt), ultrasonicating for 1 h, taking 100 μL of the mixed solution, 10 μL each time, and coating the area of ​​0.02-0.03 cm each time 2 , drop 100 μL in total ten times and evenly coat one end of a 2cm*0.5cm nickel mesh.

[0044] Example 1 :This embodiment provides a self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material and a preparation method thereof, comprising the following steps:

[0045] (1) 0.056 g of CoSO4·7H2O, 0.012 g of trimethyltetradecylammonium chloride, 1 mL of octylamine and 18 mL of hexane were added into a 20 mL reactor, mixed by ultrasonication, and heated at 140 °C for 10 h. The obtained product was collected and washed with ethanol-n-hexane in a cycle to obtain pure α-Co(OH)2 nanotubes, which were then dispersed in 10 mL of chloroform solvent.

[0046] (2) 228.8 mg of Mn3O4, 5.7 mL of oleic acid, 1.5 g of 1-octadecyl alcohol and 10 mL of 1-octadecene were mixed in a three-necked flask and heated to 200°C, and maintained at this temperature for 30 min under N2 protection. The solution was then heated to 320°C and maintained at this temperature for 30 min. When the color of the reaction solution changed dramatically, it was maintained for another 30 min to form MnO nanocrystals. The obtained nanocrystals were then washed in an ethanol-n-hexane cycle, and the final MnO nanocrystals were dispersed in 10 mL of n-hexane.

[0047] (3) The diffusion assembly method was used for assembly. 108 μL of MnO dispersion was taken and the α-Co(OH)2 nanotube dispersion was added after the solution evaporated naturally. 15 mL of ethanol was slowly dripped along the wall. After standing for 24 h, a self-assembled α-Co(OH)2 / MnO composite material was obtained. Chloroform is a benign solvent for α-Co(OH)2 nanotubes, and ethanol is a poor solvent. When ethanol is slowly added, an obvious liquid-liquid interface is formed between ethanol and chloroform. As the poor solvent diffuses, it induces the self-assembly of MnO nanocrystals and α-Co(OH)2 nanotubes.

[0048] The composite material prepared above was then collected, washed, dried, and annealed at 300°C for 30 min in an argon atmosphere. After the annealed sample was fully ground, 5 mg of the sample was added to 450 μL of ethanol, and 5 μL of naphthol solution (5% wt) was added. Ultrasonication was performed for 1 h, and 100 μL of a small amount was taken and evenly coated on one end of a 1 cm*0.5 cm nickel mesh several times. The coating area was 0.5 cm*0.5 cm. After drying, it was an α-Co(OH)2 / MnO@Ni electrode.

[0049] Comparative Example 1 :This comparative example provides an α-Co(OH)2 nanotube material and a preparation method thereof, comprising the following steps:

[0050] 0.056 g of CoSO4·7H2O, 0.012 g of trimethyltetradecylammonium chloride, 1 mL of octylamine and 18 mL of hexane were added into a 20 mL reactor, mixed evenly by ultrasonication, and heated at 140 °C for 10 h. The obtained product was collected and washed in an ethanol-n-hexane cycle to finally obtain pure α-Co(OH)2 nanotubes, which were dispersed in 10 mL of chloroform solvent.

[0051] Then the prepared α-Co(OH)2 nanotube material was collected, washed, dried, and annealed at 300℃ for 30min under argon atmosphere. After the annealed sample was fully ground, 5mg of the sample was added to 450μL of ethanol, and 5μL of naphthol solution (5%wt) was added. Ultrasonication was performed for 1h, and 100μL of the sample was evenly coated on one end of a 1cm*0.5cm nickel mesh in small amounts several times. The coating area was 0.5cm*0.5cm, and the α-Co(OH)2@Ni electrode was obtained after drying.

[0052] Comparative Example 2 :This comparative example provides a MnO nanocrystalline material and a preparation method thereof, comprising the following steps:

[0053] 228.8 mg of Mn3O4, 5.7 mL of oleic acid, 1.5 g of 1-octadecyl alcohol and 10 mL of 1-octadecene were mixed in a three-necked flask and heated to 200°C, and maintained at this temperature for 30 min under N2 protection. The solution was then heated to 320°C and maintained at this temperature for 30 min. When the color of the reaction solution changed dramatically, it was maintained for another 30 min to form nanocrystals. The obtained nanocrystals were then washed in an ethanol-n-hexane cycle, and the final MnO nanocrystals were dispersed in 10 mL of n-hexane.

[0054] Then the prepared MnO nanocrystalline material was collected, washed, dried, and annealed at 300°C for 30 min in an argon atmosphere. After the annealed sample was fully ground, 5 mg of the sample was added to 450 μL of ethanol, and 5 μL of naphthol solution (5% wt) was added, and ultrasonicated for 1 h. 100 μL of a small amount was taken and evenly coated on one end of a 1 cm*0.5 cm nickel mesh several times, with a coating area of ​​0.5 cm*0.5 cm. After drying, the MnO@Ni electrode was obtained.

[0055] Example 2 :This embodiment performs structural tests on the materials prepared in Example 1 and Comparative Examples 1 to 2

[0056] like Figure 1 As shown in (a), the nanotube length of the α-Co(OH)2 nanotube material prepared in Comparative Example 1 is 200-300 nm, the outer diameter of the tube is 16-18 nm, and the wall thickness is 1-2 nm;

[0057] like Figure 1 As shown in (b), the particle size of the MnO nanocrystalline material prepared in Comparative Example 2 is 13-15 nm;

[0058] like Figure 1 As shown in (c), the MnO nanocrystals in the α-Co(OH)2 / MnO composite material prepared in Example 1 are uniformly distributed in the α-Co(OH)2 nanotubes in the form of one-dimensional chains to form an ordered one-dimensional assembly. It can be seen from the TEM electron microscope image that the MnO nanocrystals filled in the α-Co(OH)2 nanotubes can form an open porous structure.

[0059] like Figure 1 As shown in (d), the α-Co(OH)2 / MnO composite material prepared in Example 1 shows that the one-dimensional structure can still be retained after annealing under argon protection;

[0060] like Figure 2 As shown, it can be seen from the XRD diagram that the crystal structure of the α-Co(OH)2 / MnO composite material does not change before and after annealing, and the crystal composition of the composite material is α-Co(OH)2 and MnO.

[0061] Example 3 : This example tests the electrochemical properties of the materials prepared in Example 1 and Comparative Examples 1 to 2

[0062] like Figure 3 As shown, through fitting, it is concluded that the electrochemical transfer resistance of the α-Co(OH)2 / MnO@Ni electrode is 0.447Ω, the electrochemical transfer resistance of the α-Co(OH)2@Ni electrode is 3.935Ω, and the electrochemical transfer resistance of the MnO@Ni electrode is 8.914Ω. It can be seen that the electrochemical transfer resistance of the α-Co(OH)2 / MnO@Ni electrode is the smallest, indicating that its conductivity is the best.

[0063] like Figure 4 As shown in the figure, the double layer capacitance (C dl ) is 6.34mF / cm 2 , the double layer capacitance value (C dl ) is 5.53mF / cm 2 , the double layer capacitance of MnO@Ni electrode (C dl ) is 4.56mF / cm 2 , C dl It is proportional to the electrochemical active area. Therefore, the α-Co(OH)2 / MnO@Ni electrode prepared by the present invention has a higher electrochemical active area.

[0064] Test Example 1: In this example, alkaline oxygen evolution test was performed on the IrO2@Ni commercial electrode, the electrodes prepared in Example 1 and Comparative Examples 1-2.

[0065] Experimental process: A three-electrode system was used, with the IrO2@Ni commercial electrode, the electrodes prepared in Example 1 and Comparative Examples 1-2 directly used as working electrodes, platinum sheet used as counter electrode, saturated calomel electrode used as reference electrode, and the electrolyte solution was 1 mol L - 1 KOH solution.

[0066] Linear sweep voltammetry was performed on an electrochemical workstation with a starting voltage of 0.1 V, an end voltage of 1.2 V, and a scan rate of 5 mV / s. The voltammetric curve of the working electrode was recorded, and the OER performance was tested by a linear sweep polarization curve. Among them, overpotential (η) and Tafel slope are the main performance indicators for evaluating the electrocatalytic oxygen evolution reaction. The smaller the overpotential and the smaller the Tafel slope, the higher the catalytic activity of the catalyst.

[0067] from Figure 5 It can be seen that at 50mA / cm 2 Under the current density, the electrode prepared by the α-Co(OH)2 / MnO composite material (purple curve) prepared in Example 1 has the highest performance in catalyzing the OER reaction, with an overpotential value of 310 mV and a Tafel slope of 59.62 mV / dec, while the overpotential values ​​of the IrO2@Ni commercial electrode (black curve) and the electrodes prepared in Comparative Examples 1 to 2 (red and blue curves) are 377 mV, 362 mV, and 376 mV, respectively, and the Tafel slopes are 59.62 mV / dec, 104.77 mV / dec, 89.79 mV / dec, and 97.97 mV / dec, respectively.

[0068] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material, characterized in that: The composite material comprises cobalt hydroxide nanotubes and manganese oxide nanocrystals distributed in the cobalt hydroxide nanotubes; the diameter of the cobalt hydroxide nanotubes is 12-15nm, and the average particle size of the manganese oxide nanocrystals is 11-13nm.

2. A method for preparing the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material according to claim 1, characterized in that: The steps include: S1, mixing CoSO4·7H2O and trimethyltetradecylammonium chloride in an organic solvent for solvothermal reaction to obtain α-Co(OH)2 nanotubes, and further obtaining α-Co(OH)2 nanotube dispersion; S2, mixing Mn3O4, oleic acid, 1-octadecyl alcohol and 1-octadecene for heating reaction to obtain MnO nanocrystals, and further obtaining a MnO nanocrystal dispersion; S3. After the MnO nanocrystal dispersion is naturally volatilized, α-Co(OH)2 nanotube dispersion is added, and ethanol is added, and after standing, a self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material is obtained.

3. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of CoSO4·7H2O to trimethyltetradecylammonium chloride is 4-5:1; In step S2, the usage ratio of Mn3O4, oleic acid, 1-octadecyl alcohol and 1-octadecene is 0.2-0.25 g: 5-6 mL: 1.2-1.6 g: 8-12 mL.

4. The preparation method according to claim 2, characterized in that: In step S1, the organic solvent is selected from one or more of octane, hexane or a mixed solvent of octane and hexane; the heating reaction temperature is 120-150° C. and the time is 8-15 hours; Preferably, the organic solvent is a mixed solvent of octane and hexane, and the volume ratio of octane to hexane in the mixed solvent is 1:17-20; Preferably, the product obtained by the heating reaction is washed in an ethanol-n-hexane cycle to finally obtain pure α-Co(OH)2 nanotubes, and then dispersed in a chloroform solvent to obtain an α-Co(OH)2 nanotube dispersion.

5. The preparation method according to claim 2, characterized in that: In step S2, the heating reaction is first heated to 180-220° C., kept warm for 25-35 minutes, then heated to 300-350° C., kept warm for 25-35 minutes, and kept warm for another 25-35 minutes when the color of the reaction solution changes, to form MnO nanocrystals.

6. The preparation method according to claim 2, characterized in that: In step S2, the heating reaction is carried out under an inert atmosphere; the product obtained by the heating reaction is washed by ethanol-n-hexane cycle to finally obtain MnO nanocrystals, and dispersed in n-hexane to obtain a MnO nanocrystal dispersion; Preferably, the inert atmosphere is selected from one or more of hydrogen, nitrogen and argon.

7. The preparation method according to claim 2, characterized in that: In step S3, the standing time is 20 hours to 40 hours, preferably 24 hours; the product after standing is washed, dried, and annealed to obtain a self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material; Preferably, the annealing temperature is 280-350° C. and the time is 25-40 min.

8. A working electrode, comprising the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material according to claim 1; Preferably, the working electrode is prepared by adding ground α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material into an ethanol solution, mixing with a binder solution, and then ultrasonically treating the mixture, coating the obtained slurry on a nickel mesh, and drying the mixture.

9. Use of the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material according to claim 1 and / or the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material prepared by the preparation method according to any one of claims 2 to 7 as an oxygen evolution electrode.

10. Use of the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material according to claim 1 and / or the self-assembled α-cobalt hydroxide / manganese oxide composite electrocatalytic oxygen evolution material prepared by the preparation method according to any one of claims 2 to 7 in the field of hydrogen production by electrolysis of water.